Pengaruh Jacobson’s Progressive Muscular Relaxation terhadap Kualitas Tidur Pada Lansia Di UPT Kesejahteraan Sosial Lanjut Usia Budi Agung - Dyah G. R. Kareri; Derri R. Tallo Manafe; Maria Kurniati Ester Payon (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACT Background: The quality of sleep in elderly tend to decline. This occurs as a result of certain changes such as physical, biological, mental and socio-economic. The quality of sleep may influence the healthcondition for short or long terms. Poor quality of sleep may cause difficulty in concentrating, slow response, memory disturbance and decrease of performance in daily life. The decline of sleep qualitymay be resolved with Jacobson’s Progressive Muscular Relaxation (JPMR) exercise. Objective: To analyze the effect of Jacobson’s Progressive Muscular Relaxation on sleep quality inelderly at Budi Agung Social Institution. Methods: This study is a pre experimental study with one group pretest-posttest design. The subject ofthis study were the 19 elderly at Budi Agung Social Institution. In this study, JPMR exercise was done in5 days. Sleep quality before and after JPMR exercise was measured using Pittsburgh Sleep Quality Index(PSQI) questionnair. The data obtained was analyzed using McNemar test. Results: From a total of 19 subjects, 3 subjects had good sleep quality while 16 subjecst had poor sleepquality. On the other hand, after the JPMR excercise, improved sleep qualiy was found in the 16 subjectswhile the 3 subjects still had poor sleep quality; bivariate analysis p value = 0.002 (p <0.05). Conclusion: Jacobson’s Progressive Muscular Relaxation (JPMR) has a significant effect on sleepquality in elderly at Budi Agung Social Institution. Keywords: elderly, sleep quality, Jacobson’s Progressive Muscular Relaxation, Pittsburgh Sleep QualityIndex.